2020
DOI: 10.1080/23322039.2020.1821482
|View full text |Cite
|
Sign up to set email alerts
|

The effect of economic policy uncertainty and herding on leverage: An examination of the BRICS countries

Abstract: This study examines the role of economic policy uncertainty (EPU) in influencing firm performance and leverage as a form of financing decisions, in the presence of herding in the emerging markets of Brazil, Russia, India, China and South Africa (BRICS). This study contributes to our understanding of how businesses in emerging markets make financial decisions during uncertain times as well as the role of policy development in influencing firm performance and corporate decisions. The increase or decrease in EPU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…By contrast 17 of the 58 conference papers that address livestock issues focus on some aspect of intensive livestock production (2.8% of the 622 conference papers), but none of them in Botswana, Namibia, or South Africa. While the literature on megatrends makes mention of “policy making” and “democratic development,” these are minority views, and seldom unpacked. Yet there is widespread realization of the destructive role that policy uncertainty can play in an economy (e.g., Faku & Moeti, 2020 and Gumata & Ndou, 2019 in South Africa, and Makololo & Seetharam, 2020 in the BRICS countries), whether macroeconomic policy or sector policies. As we have seen, some two thirds of the research outputs investigated here does recommend some sort of action by the state.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast 17 of the 58 conference papers that address livestock issues focus on some aspect of intensive livestock production (2.8% of the 622 conference papers), but none of them in Botswana, Namibia, or South Africa. While the literature on megatrends makes mention of “policy making” and “democratic development,” these are minority views, and seldom unpacked. Yet there is widespread realization of the destructive role that policy uncertainty can play in an economy (e.g., Faku & Moeti, 2020 and Gumata & Ndou, 2019 in South Africa, and Makololo & Seetharam, 2020 in the BRICS countries), whether macroeconomic policy or sector policies. As we have seen, some two thirds of the research outputs investigated here does recommend some sort of action by the state.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already investigated the impact of EPU on different markets (Hung, 2021; Zhu et al ., 2021; Chen et al ., 2020; Huang et al ., 2020; Makololo and Seetharam, 2020; Nguyen and Schinckus, 2020; Rong. Li et al ., 2020; Balcilar et al ., 2017; Li et al ., 2016; Wu et al ., 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Indian context, a significant number of published articles have also examined the influence of economic uncertainty on stocks (Rong. Li et al ., 2020; Makololo and Seetharam, 2020; Wu et al ., 2016). However, there is a gap in considering Indian EPU, stock, gold and crude oil prices in the Indian market in a single piece of work.…”
Section: Introductionmentioning
confidence: 99%
“…In Makololo and Seetharam's [14] research focusing on EPU's effect on leverage in BRICS countries, they found that EPU is significant in determining leverage financing decisions in Russian, Indian, and South African companies, after analyzing the top 80 listed firms in each respective country from the beginning of June 2002 to the end of June 2017. However, contrary results in Brazilian and Chinese firms appeared, which is not anticipated.…”
Section: Hypothesis Developmentmentioning
confidence: 99%